Celebrating Howard Watkins' 40th Birthday in Backyard - Watkins, Howard::::::::: (1987)
Michael Bigelow, Albert Watkins wearing hat with two beer can holders, Gene Zack, Jim Kratzer and Joe Floyd Asher